Unilateral cortical thickening and hyper-intensity due to mitochondrial encephalopathy, lactic acidosis, and stroke like episodes (MELAS) - Hatamian, Hamid Reza; Bakhshayesh, Babak; Rahman-A, Nazanin (International Clinical Neuroscience Journal, 2014)
Patients with mitochondrial encephalopathy, lactic acidosis and stroke-like episodes (MELAS) present with recurrent and partially reversible neurological deficits. Lesions of MELAS classically cause a signal change in both the grey and white matter, predominantly in the occipital and parietal lobes. These lesions mimic infarction. Here, we reported a case of MELAS with rare neuroimaging finding of hemispheric cortical thickening on T2/FLAIR images with intracortical nodular gadolinium enhancement; then we discussed the clinical and radiological differential diagnoses of it.